Cyberbullying Involvement: Impacts of Violence Exposure in The Media, Family, Society, and School - Yuliati, Reny; Saptyasari, Andria (JURNAL KOMUNIKASI INDONESIA, 2019)
Cyberbullying is a severe problem which may occur in adolescents during online communication. They may become a perpetrator or victim. This research investigates the violence exposure in several contexts, such as media, family, society, and school, and its relationship to the students’ involvement, whether they are the cyberbullying perpetrator or victim. A survey of senior high school students (N total = 201) was conducted. The study found that violence exposure, especially in the media and schools, significantly segregated the students’ cyberbullying involvement status. Youngsters, who are exposed to the violence in the media and schools, tend to be the cyberbullying perpetrator-victim. Additional analysis of the participants’ genders showed a significant difference, where female was more likely to be the cyberbullying victim and male was inclined to be the perpetrator (p < 0.05). Finally, the implications for practice and suggestions for future research are briefly addressed.